Control system of Dahlander Motor using Programmable Logic Controller based on Human Machine Interface and Internet of Things - ALWI, ZIKRI; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
The Dahlander motor is a three-phase induction motor capable of operating at two distinct rotational speeds by altering the stator winding configuration between star (Y) and delta (Δ). This dual-speed feature is essential for industrial machines such as cranes, lathes, and conveyors that require variable speed operation. However, conventional manual control methods are still widely used, posing risks to operational efficiency and safety. This study presents the design and implementation of an automated control system for a 1.3 kW Dahlander motor using a Siemens S7-1200 Programmable Logic Controller (PLC), a KTP 700 Comfort Human Machine Interface (HMI), and an Internet of Things (IoT) platform based on Node-RED. The system supports remote control via HMI panels, personal computers, and smartphones through a web-based interface using the Profinet protocol. The control logic is developed in the TIA Portal environment, enabling selection between low-speed and high-speed modes. Experimental results demonstrate that the system effectively controls motor speed with accurate and stable operation. The integration of HMI and IoT provides real-time remote monitoring and control capabilities, enhancing operational reliability and minimizing human error. This integrated system offers a cost-effective and adaptive solution for local industries, especially small and medium-sized enterprises, to embrace Industry 4.0 technologies